2013
DOI: 10.2174/0929867311320100007
|View full text |Cite
|
Sign up to set email alerts
|

Serenoa Repens, Lycopene and Selenium: A Triple Therapeutic Approach to Manage Benign Prostatic Hyperplasia

Abstract: Benign prostatic hyperplasia (BPH) is a major health concern that is likely to have an increasing impact in line with the gradual aging of the population. BPH is characterized by smooth muscle and epithelial proliferation primarily within the prostatic transition zone that can cause a variety of problems for patients, the most frequent are the lower urinary tract symptoms. BPH is thought to involve in disruption of dihydrotestosterone (DHT)-supported homeostasis between cell proliferation and cell death, and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…In aging cells, the expression of Bcl-2 is decreased and the expression of Bax is elevated [13,17]. Our study showed that D-gal significantly decreased Bcl-2 expression in the aging group while Kn administration restored Bcl-2 expression.…”
Section: Discussionmentioning
confidence: 70%
“…In aging cells, the expression of Bcl-2 is decreased and the expression of Bax is elevated [13,17]. Our study showed that D-gal significantly decreased Bcl-2 expression in the aging group while Kn administration restored Bcl-2 expression.…”
Section: Discussionmentioning
confidence: 70%
“…see Minutoli et al, 2013). All these results suggest that selenium and lycopene increase saw palmetto efficacy in BPH.…”
Section: Some Combinationsmentioning
confidence: 80%
“…This association is also more effective than saw palmetto in reducing prostate hyperplasia, in enhancing the pro‐apoptotic B ascx and caspase‐9 and suppressing the epidermal growth factor and vascular endothelial growth factor expressions in BPH (for ref. see Minutoli et al ., ). All these results suggest that selenium and lycopene increase saw palmetto efficacy in BPH.…”
Section: Nutraceuticalsmentioning
confidence: 97%
“…SeR, an extract from the berry of the American saw palmetto or dwarf palm plant [118,119,120,121], induces evident LUTS relief. Its proposed mechanisms of action are the following: (i) antiestrogenic and antiandrogenic effects [122] by weakly inhibiting the conversion of T to DHT [123]; (ii) modulation of apoptosis [78,124]; (iii) inhibition of 5-ARIs in the stroma and epithelium of the prostate [125]; and (iv) relaxation of smooth muscle cells of the detrusor through interaction with α1-adrenergic receptors [126].…”
Section: Phytotherapic Supplementsmentioning
confidence: 99%
“…Also growth factors, such as vascular endothelial growth factor (VEGF) and epidermal growth factor (EGF), were inhibited by treatment with Se-Ly-SeR combination [113,120] (Figure 1). …”
Section: Phytotherapic Supplementsmentioning
confidence: 99%